1989
DOI: 10.1136/vr.125.10.253
|View full text |Cite
|
Sign up to set email alerts
|

Ovine infectious keratoconjunctivitis: a microbiological study of clinically unaffected and affected sheep's eyes with special reference to Mycoplasma conjunctivae

Abstract: In a field survey of ovine infectious keratoconjunctivitis, the microbiological flora of 240 clinically unaffected eyes from sheep in 10 flocks was compared with the flora of an equivalent number of clinically affected eyes from 12 natural outbreaks of the disease. Totals of 16 and 17 genera of bacteria were recovered from unaffected and affected eyes, respectively. Staphylococcus, bacillus and branhamella were isolated significantly more often than the other genera of bacteria, in both the unaffected and affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 0 publications
1
37
1
1
Order By: Relevance
“…Inflammatory reaction by the phagocytic cells may have caused the keratitis. Egwu et al [21] reported isolation of S . aureus from ovine keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory reaction by the phagocytic cells may have caused the keratitis. Egwu et al [21] reported isolation of S . aureus from ovine keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic treatment may fail to eliminate M conjunctivae from the eye 3 and repeated gathering and handling of sheep for treatment encourages further spread. M conjunctivae can also be isolated from clinically normal eyes 4 . Ten gimmers had been purchased in January and were a possible source of infection.…”
Section: Small Ruminantsmentioning
confidence: 99%
“…Four swabs were submitted in total and Moraxella species were cultured in each case. This bacterium can be detected in clinically normal eyes but studies have shown that it is isolated more frequently from affected eyes (Egwu and others 1989). SAC C VS considered that the Moraxella species represented an incidental secondary infection and was not responsible for the relapses.…”
Section: Small Ruminantsmentioning
confidence: 99%